The equity mindset designing human spaces through journeys, reflections, and practices - Ike, Ifeomasinachi (Ascent Audio, 2024)
In The Equity Mindset, Ifeomasinachi Ike delivers a moving and impactful exploration of why equity is so important, the shortcomings of institutional diversity and inclusion (D&I) initiatives, and how we creatively and boldly design cultures centering the expertise of those who know firsthand how inequity has shaped work culture. The book examines the dynamics of normalized institutional oppression, offers real-world case studies, and provides listeners with new practices, key performance indicators (KPIs), and milestones for measuring the success of modern DEI efforts. At its core, The Equity Mindset is about adopting a problem-solving mentality to address social inequities to ensure we all thrive. This book also includes practitioner interviews with guidance on how each person, regardless of industry, can advance equity personally and professionally; strategies for addressing organizational bias, inequity, and lack of representation; and tools for leaders and decisionmakers seeking concrete steps to create safer cultures for historically marginalized communities. A can't-miss resource for managers, executives, board members, and other business leaders, The Equity Mindset is for those with and without traditional authority who seek to advance the movement for equitable treatment in every environment.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Organizational change; Equality; Changement organisationnel; Audiobooks; Livres audio